Pediatric ENT Infections - Ophthalmological Perspective on Pediatric Ear, Nose, and Throat Infections - ÖZDEMİR, MEHMET HAKAN; Kırık F.; Özdemir M. H. (Springer, London/Berlin, 2021)
The majority of the tissues and organs that fall into the area of expertise of ear, nose and throat (ENT) specialists are adjacent to the orbit, and therefore to the globe. As a result of this contiguity, ENT diseases can spread to the orbit and present with various orbital complications. While these complications can be mild, they can also manifest as severe morbidities that lead to permanent loss of vision. In addition, ENT diseases can also spread to the cranium as well as the orbit, and lead to severe intracranial complications that may result in mortality. Such intracranial complications may also manifest with findings in an ophthalmological examination, as many cranial nerves (CNs) are also associated with the orbital structures. This is why ENT specialists commonly encounter ophthalmological findings as a result of both the orbital and cranial complications of infectious ENT diseases. In addition, ophthalmological examination findings are useful for diagnosis, as some infectious agents can cause a common infection both in the ocular and head-neck regions.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Enfeksiyon; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Pediatrics Infectious Diseases; Surgery Medicine Sciences; Eye Diseases and Surgery; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; KULAK BURUN BOĞAZ; GÖZ HASTALIKLARI; PEDİATRİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; OTORHINOLARYNGOLOGY; OPHTHALMOLOGY; PEDIATRICS; MEDICINE, GENERAL & INTERNAL; Konuşma ve İşitme; Optometri; Genel Sağlık Meslekleri; Pediatri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Pediatri, Perinatoloji ve Çocuk Sağlığı; Oftalmoloji; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Speech and Hearing; Optometry; General Health Professions; Pediatrics; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Pediatrics, Perinatology and Child Health; Otorhinolaryngology; Ophthalmology; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine